1980
DOI: 10.3758/bf03197552
|View full text |Cite
|
Sign up to set email alerts
|

Active memory processes in visual sentence comprehension: Clause effects and pronominal reference

Abstract: Two experiments were conducted to investigate active memory processes during reading. Subjects read two-clause sentences one word at a time at a self-paced rate. Following each sentence a probe word was presented; subjects were to decide if this word occurred in the sentence they had just read. The first experiment examined clausal effects during reading. Reaction times to items from the final clause were shorter than those to items from a previous clause even when the same number of words intervened. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
3
3

Year Published

1985
1985
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 11 publications
10
107
3
3
Order By: Relevance
“…The strongest languagebased demonstrations of greater surface information loss after crossing constituent boundaries have been those where crossing boundaries was not confounded with other measures of the test interval. The stimuli in these studies were constructed so that the same number of items (words, clauses, or sentences) intervened between a target's original occurrence and its subsequent test whether or not a boundary was crossed (Caplan, 1972, Experiment 4;Chang, 1980, Experiment 1). To provide an equally strong nonverbal demonstration, the present stimuli were also constructed this way.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strongest languagebased demonstrations of greater surface information loss after crossing constituent boundaries have been those where crossing boundaries was not confounded with other measures of the test interval. The stimuli in these studies were constructed so that the same number of items (words, clauses, or sentences) intervened between a target's original occurrence and its subsequent test whether or not a boundary was crossed (Caplan, 1972, Experiment 4;Chang, 1980, Experiment 1). To provide an equally strong nonverbal demonstration, the present stimuli were also constructed this way.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a series of studies by Jarvella demonstrated that words in the most recently processed constituent had the highest probability of being remembered verbatim; such exact memory declined dramatically for words prior to the last constituent boundary (Jarvella, 1970(Jarvella, , 1971(Jarvella, , 1973(Jarvella, , 1979Jarvella & Herman, 1972;Jarvella, Snodgrass, & Adler, 1978; see also Marslen-Wilson & Tyler, 1976). Caplan (1972) and Chang (1980) demonstrated that a previously seen or heard word was verified more rapidly when the constituent structure of its sentence placed it in its final, as opposed to next-to-final clause. Clark and Sengul (1979) demonstrated that identifying the referent of a pronoun (she) or definite noun phrase (the woman) occurred more smoothly when the implied referent was explicitly mentioned in the previous clause; if mentioned even two clauses earlier, momentary processing difficulties were experienced.…”
Section: Surface Information Loss and Constituent Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This view is in stark contrast to one emerging from probe-word tasks, a method in which subjects are asked to judge as quickly as possible whether a word has occurred in the preceding text (sentence or discourse). Studies using that technique have shown that repeated-name coreference speeds responses to probes consisting of the repeated name and slows responses to probes consisting of a name from the text that was not repeated; pronominal coreference does not immediately have such effects (Chang;Corbett & Chang, 1983; Gemsbacher, 1989;MacDonald & MacWhinney, 1990). In fact, one series of studies showed that pronouns have no effect on reponses to probe words leading to the conclusion that pronouns are not interpreted at all by the automatic processes responsible for basic understanding in reading (Greene, McKoon, & Ratcliff, 1992).…”
Section: Psycholinguisticsmentioning
confidence: 99%
“…The occurrence of an anaphoric pronoun appears to activate several candidate antecedents immediately at or after the pronoun (Corbett & Chang, 1983;1989;MacDonald & MacWhinney, 1990;Smyth, 1986;Tyler & Marslen-Wilson, 1982). However, several studies have found that at various time lags after the pronoun, the correct antecedent has become more available than the incorrect one (Chang, 1980;Gernsbacher, 1989;MacDonald & MacWhinney, 1990;Stevenson, 1986). Gernsbacher (1989) has proposed that the change in activation level of candidate antecedents over time can be explained by the enhancement of the correct antecedent and the active suppression of incorrect candidates.…”
mentioning
confidence: 99%